OWNERSHIP STRUCTURES AND SOCIAL DISCLOSURES IN THE TOURISM SECTOR: THE MODERATING ROLE OF INDEPENDENT COMMISSIONERS - Vionna Natasya Elyson; Supatmi Supatmi (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2025)
This research aims to analyze the influence of ownership structure on social disclosure moderated by independent commissioners. The research samples were 47 companies in the tourism industry listed on the Indonesia Stock Exchange in 2020-2022 with a total of 141 observations. The ownership structure is measured by the percentage of institutional, managerial and foreign share ownership. While social disclosure is measured using 39 indicators of social disclosure according to the Global Reporting Initiative (GRI), which are measured by weighting between a score of 0 to 2. Independent commissioners are measured based on the number of independent commissioners in the company. As the panel data regression analysis, this research found that only managerial ownership could encourage social disclosure carried out by the tourism industry during the pandemic period. Institutional ownership was not proven to influence social disclosure. However, the foreign ownership had a positive effect on social disclosure after being moderated by independent commissioners. Independent commissioners were found to strengthen the impact of foreign ownership on social disclosure. These findings support the legitimacy theory, which states that to strengthen public legitimacy, company shareholders, especially shares owned by managers and foreign parties, can take advantage of social disclosure and increase the role of independent commissioners in the company.